Weapons of Moths against Bats and Their Bionic Applications - Jia Tianqi (BIO Web of Conferences)
The evolutionary arms race between moths and bats has spurred the development of intricate defense mechanisms in moths, which are not only crucial for their survival but also serve as a rich source of inspiration for biomimetic innovations. This study delves into the array of biological “weapons” that moths employ to evade bat predation, including behavioral adaptations, acoustic properties of wing scales, chemical defenses, and acoustic strategies. By presenting a comprehensive overview of these defense tactics, we lay the groundwork for understanding how these biological insights translate into groundbreaking applications in modern science and technology. The review begins with an exploration of passive defenses such as behavioral changes and the acoustic absorption capabilities of moth wing scales, which significantly reduce detection by bats. It then transitions into active defense strategies, such as the production of ultrasonic clicks for sonar interference and the execution of evasive flight maneuvers. These natural strategies are then extended into the realm of biomimetics, where we examine the development of innovative technologies like directional hearing aids and acoustic metamaterials, inspired by the auditory systems and wing structures of moths. By framing biomimetic applications as a direct extension of the moth's defense mechanisms, this study aims to provide a clear link between biological adaptations and their technological counterparts. The research underscores the potential of moth-inspired designs to enhance acoustic imaging, environmental monitoring, and medical diagnostics, ultimately highlighting the mutually beneficial relationship between the study of nature and the advancement of human technology.